2015
DOI: 10.5713/ajas.14.0924
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Oxidized Soybean Oil Increased Intestinal Oxidative Stress and Affected Intestinal Immune Variables in Yellow-feathered Broilers

Abstract: This study investigated the effect of oxidized soybean oil in the diet of young chickens on growth performance and intestinal oxidative stress, and indices of intestinal immune function. Corn-soybean-based diets containing 2% mixtures of fresh and oxidized soybean oil provided 6 levels (0.15, 1.01, 3.14, 4.95, 7.05, and 8.97 meqO2/kg) of peroxide value (POV) in the diets. Each dietary treatment, fed for 22 d, had 6 replicates, each containing 30 birds (n = 1,080). Increasing POV levels reduced average daily fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 22 publications
4
37
0
Order By: Relevance
“…In the present study, T-SOD levels both inileum (d 14 and 21) and liver (d 21) and the expression of CAT gene in ileum significantly decreased when oxidized oils were fed. These results were consistent with those reported in another oxidative stress study (Liang et al, 2015). The present study demonstrated that feeding oxidized oil decreased the activity of antioxidation enzymes (T-SOD), indicating the lower capacity of scavenging free radicals, and suggested that the oxidized oil might cause metabolic oxidative stress in intestine of broiler chickens.…”
Section: Effect Of Oxidized Soybean Oils On Oxidative Status and Intesupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, T-SOD levels both inileum (d 14 and 21) and liver (d 21) and the expression of CAT gene in ileum significantly decreased when oxidized oils were fed. These results were consistent with those reported in another oxidative stress study (Liang et al, 2015). The present study demonstrated that feeding oxidized oil decreased the activity of antioxidation enzymes (T-SOD), indicating the lower capacity of scavenging free radicals, and suggested that the oxidized oil might cause metabolic oxidative stress in intestine of broiler chickens.…”
Section: Effect Of Oxidized Soybean Oils On Oxidative Status and Intesupporting
confidence: 93%
“…Our data showed that the dietary inclusion of highlyoxidized soybean oil increased the concentration of MDA in the jejunum and the liver, indicating lipid peroxidation in these tissues. Similar results were obtained in pigs (Ringseis et al, 2007) and broilers (Zhang et al, 2011;Liang et al, 2015). MDA level changes observed in the birds fed oxidized oils maybe triggered by free radicals of lipid peroxidation.…”
Section: Effect Of Oxidized Soybean Oils On Oxidative Status and Intesupporting
confidence: 84%
“…The peroxidation of lipids forms hydroxiperoxyde, an intermediate compound, and aldehydes, ketones, dicarbonyls, furans and hydrocarbons, as secondary products [55]. Toxic effects of the hydroperoxyde and the secondary products have already been known for a long time in the literature [56][57][58][59].…”
Section: Oxidized Oilmentioning
confidence: 99%
“…Dibner and collaborators [56] observed that the inclusion of oxidized poultry fat in broiler feed results in the reduction of body weight, hematocrit, and the enterocyte life span, as well as increases hepatocytes proliferation and reduced the effectiveness of secretory IgA in the intestine. The increased peroxide value (POV) in the diet produced deleterious effects not just on performance but also affected gut associated lymphoid tissue (GALT) [57,58]. Furthermore, Liang and colleagues observed that the jejunum suffered oxidative stress by the oxidized oil present in the diet, which affected cytokine expression and immune cells in the tissue.…”
Section: Oxidized Oilmentioning
confidence: 99%
See 1 more Smart Citation